If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3) + -6 = -3y Multiply 2 * 3 6 + -6 = -3y Combine like terms: 6 + -6 = 0 0 = -3y Solving 0 = -3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '3y' to each side of the equation. 0 + 3y = -3y + 3y Remove the zero: 3y = -3y + 3y Combine like terms: -3y + 3y = 0 3y = 0 Divide each side by '3'. y = 0 Simplifying y = 0
| ln(x)=56 | | 1.5y-x=-6 | | -18+9r-6r+4= | | 0=x^5+5x^4-2x^3-24x^2 | | y=4x^2+10x-4 | | 36+5t=-12-3t | | 5n-8=4n+2n | | g(c+1)=x+4 | | 2(x+3)+3x=-3(x-2)+8x | | 9.2x-18.4=8.9x-53.4 | | f(x)=6x^2+78 | | -72x=20x+92 | | 26=-68x+42x | | 6v^2-11v-35=0 | | 3a-4b+c-d=0 | | ln(x+6)+ln(x+5)=ln(5) | | f(x)=2x^4-x^3+49x^2-25x-25 | | n-1.4n-1=6(n-2.3) | | C-32=71 | | x+(x+40)=110 | | 2ln(lnx)-ln(5lnx-6)=0 | | a-6.6=10.1 | | -17x+2(x+14)=-2 | | y^2=x^2-x^4 | | (X^8)-1=0 | | R+4=12 | | 6n+45=4n-15 | | f(x+4)=8(x+4)-2 | | (8+z)(5z+9)=0 | | -2-3x+5=16+2x+22 | | .75x=.51 | | 8.5x-12=6.5x-18 |